Fate of arsenicals in mice carrying the human AS3MT gene exposed to environmentally relevant levels of arsenite in drinking water - Douillet, Christelle; Miller, Madison; Cable, Peter H; Shi, Qing; El-Masri, Hisham; Matoušek, Tomáš; Koller, Beverly H; Thomas, David J; Stýblo, Miroslav (Scientific reports, 2023)
Although mice are widely used to study adverse effects of inorganic arsenic (iAs), higher rates of iAs methylation in mice than in humans may limit their utility as a model organism. A recently created 129S6 mouse strain in which the Borcs7/As3mt locus replaces the human BORCS7/AS3MT locus exhibits a human-like pattern of iAs metabolism. Here, we evaluate dosage dependency of iAs metabolism in humanized (Hs) mice. We determined tissue and urinary concentrations and proportions of iAs, methylarsenic (MAs), and dimethylarsenic (DMAs) in male and female Hs and wild-type (WT) mice that received 25- or 400-ppb iAs in drinking water. At both exposure levels, Hs mice excrete less total arsenic (tAs) in urine and retain more tAs in tissues than WT mice. Tissue tAs levels are higher in Hs females than in Hs males, particularly after exposure to 400-ppb iAs. Tissue and urinary fractions of tAs present as iAs and MAs are significantly greater in Hs mice than in WT mice. Notably, tissue tAs dosimetry in Hs mice resembles human tissue dosimetry predicted by a physiologically based pharmacokinetic model. These data provide additional support for use of Hs mice in laboratory studies examining effects of iAs exposure in target tissues or cells.
Keywords: Humans; arsenikové přípravky; Methyltransferases; Female; lidé; zvířata; myši; Arsenites; Mice; arsenitany; pitná voda; Arsenicals; ženské pohlaví; Male; arsen; Arsenic; Animals; mužské pohlaví; methyltransferasy; Drinking Water